Human Cytomegalovirus Latency: Targeting Differences in the Latently Infected Cell with a View to Clearing Latent Infection. (4th June 2014) - Poole, Emma; Wills, Mark; Sinclair, John
Abstract : Human cytomegalovirus (HCMV) is a human herpesvirus which causes little or no disease in the immunocompetent. However, in immunocompromised individuals, neonates, or patients on immune suppressive therapies, HCMV can cause significant morbidity and mortality in some patient groups. As with all herpesviruses, HCMV has two life cycle phases: a productive phase, where new virions are produced and a latent phase where there is a restricted gene transcription profile and no new virion production. Currently available antivirals target the productive phase of HCMV infection and, although these have greatly decreased the severity of HCMV-induced disease in immunocompromised or immunosuppressed individuals, they often have associated toxicities, routinely result in selection of drug resistant viral mutants, and, importantly, they do not target cells latently infected with virus. Thus, there is a real need to derive novel antiviral therapies which, not least, are also able to target latent infection. In this paper, we describe recent work which has begun to analyse changes in the cell associated with latent infection and the possibility that these latency-associated changes in cell phenotype could be targeted by novel chemo- or immunotherapeutic strategies in order to diminish, or even clear, latent infection at least in some specific clinical settings.